2022
DOI: 10.1016/j.appdev.2022.101390
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: Psychological symptoms and coping strategies in preschoolers, schoolchildren, and adolescents

Abstract: The present study aimed to compare psychological symptoms and coping strategies in 1480 preschoolers, schoolchildren, and adolescents during home confinement due to COVID-19. We enrolled parents from Italy, Portugal, and Spain who completed a survey between the second and fourth week of lockdown. The results showed that preschoolers displayed more sleeping difficulties, temper tantrums, and dependency while adolescents' reactions were more related to COVID-19 worries and uncertainty. Schoolchildren showed more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 75 publications
3
9
1
3
Order By: Relevance
“…They found that task-oriented coping was the most widely reported coping mechanism by school-age children during the pandemic. While, the study finding of Delvecchio et al, (2022) is contradicted with the result of the present study as they found that the school-age children's use of emotionfocused techniques may be linked to their common imitation in play, drawings, and stories of their fears and worries, which are normal activities at this stage .…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…They found that task-oriented coping was the most widely reported coping mechanism by school-age children during the pandemic. While, the study finding of Delvecchio et al, (2022) is contradicted with the result of the present study as they found that the school-age children's use of emotionfocused techniques may be linked to their common imitation in play, drawings, and stories of their fears and worries, which are normal activities at this stage .…”
Section: Discussioncontrasting
confidence: 99%
“…It could be due to the male children at this stage are very physically active than female and interested in playing, while social isolation restricted their movements. This finding is congruent with Delvecchio et al, (2022), who studied the psychological effects of COVID-19 and coping mechanisms of preschool, school-age children, and adolescent, and mentioned that stress was higher in males at school age, while it peaked in adolescence in females. On the contrary, the study findings of McKune et al, (2021) revealed that the frequency of those exhibiting psychosocial stress symptoms, were markedly greater among females .…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Notably, adolescents have experienced the results of governments and communities failing to address the impact of structural violence and racism. Though the full extent of the impact of racism and other structural inequities, as well as the effects of COVID-19 pandemic, on developing youth has yet to be quantified, increased hospitalizations and diagnoses suggest that anxiety, fear, anger, loneliness, and grief associated with these events has led to toxic stress for many adolescents [ 16 ••, 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%